1967
DOI: 10.1002/1097-4679(196707)23:3<375::aid-jclp2270230324>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the Harris revision of the Goodenough Draw-A-Man Test

Abstract: PROBLEMIn 1963, Harris in his book on Children's Drawings(2) published a revision and re-evaluation of the Goodenough Draw-a-Man Test. The revision consisted mainly of adding 22 new scoring categories to the original 51 categories developed by Goodenough and in devising a Draw-a-Woman Scale which paralleled the Drawa-Man Scale. He presented two separate scoring systems, one for the Man and one for the Woman. I n addition, Harris developed a Quality Scale by which an I& for the Draw-a-Man and Draw-a-Woman Tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1968
1968
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 1 publication
2
15
0
Order By: Relevance
“…Greater differences in the scores of boys and girls on the DAM were found in the two studies investigating this variable (Sells, 1966;Vane, 1967). Boy/ girl differences on the DAM ranged from about 1 to about 11 standard score points; sex differences on the GH ranged from approximately 1 to less than 3 standard score points.…”
Section: Criterion Validitysupporting
confidence: 88%
See 1 more Smart Citation
“…Greater differences in the scores of boys and girls on the DAM were found in the two studies investigating this variable (Sells, 1966;Vane, 1967). Boy/ girl differences on the DAM ranged from about 1 to about 11 standard score points; sex differences on the GH ranged from approximately 1 to less than 3 standard score points.…”
Section: Criterion Validitysupporting
confidence: 88%
“…Goodenough DAM standard deviations 3 to 5 standard score points greater than GH Man scale deviations were observed in three of four studies assessing this variable (Levine 6 Gross, 1968;Phillips et al, 1973;Sells, 1966;Vane, 1967). Greater differences in the scores of boys and girls on the DAM were found in the two studies investigating this variable (Sells, 1966;Vane, 1967).…”
Section: Criterion Validitymentioning
confidence: 99%
“…In some studies, DAPT performances were positively correlated with IQ (e.g., Dunn, 1967;Durrett, 1972;Johnson & Johnson, 1971;Tramill, Edwards, & Tramill, 1980;White, 1979). Other studies and reviews, however, reported conflicting evidence (Lehman & Levy, 1971;Scott, 1981;Vane, 1967). Only one study (Croake, Keller, & Catlin, 1973) compared all three (man, woman, and self) human figure drawings with WPPSI performance; the results of that study, which indicated that the man drawing correlated more highly with IQ performance than did the other two figure drawings, are inconsistent with other reports (Harris, 1963;Milkovitch & Landry, 1983;Scott, 1981).…”
Section: Discussionsupporting
confidence: 75%
“…Sinha (1970) reports a wide range of correlations between the Harris Scale and a number of group measures of verbal and non-verbal ability. The correlations with Stanford-Binet in Tables 2 and 3 are similar to those reported from America (Vane, 1967); and from South Africa, Strumpfer and Mienie (1968) reported a correlation of 0-54 with an individual intelligence test among children of average age 11-4 yr. Pringle and Pickup (1963), who gave the Goodenough test to 37 English school children each year from 7-to 10-years of age, obtained correlations with StanfordBinet in the range 0-11-0-37. American studies reporting relationships between these measures (Estes et al, 1961;Thompson and Finlay, 1963;Vane and Kessler, 1964;Muzerkari, 1967) have generally used samples with a narrower range of ability and a less restricted age range than the present study.…”
Section: Concurrent Validitymentioning
confidence: 99%